1982
DOI: 10.7326/0003-4819-96-5-565
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intravenous Vasopressin in Active Upper Gastrointestinal Bleeding

Abstract: Sixty patients with active upper gastrointestinal bleeding were randomized to received either continuous intravenous infusions of vasopressin (29 patients) or placebo (31 patients) at a rate of 40 U/h. Six hours after beginning the study, 13 patients in the vasopressin group and 11 in the placebo group] had ceased bleeding (p = 0.46). By 24 hours. 17 patients in the vasopressin group and 14 in the placebo group had stopped bleeding (p = 0.30). Restriction of the analysis to patients bleeding from varices showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(36 citation statements)
references
References 15 publications
0
33
2
1
Order By: Relevance
“…Some of these side effects were because of the powerful vasoconstrictor action of ornipressin, and were similar to the complications observed in therapeutic trials of vasopressin in cirrhotic patients with gastrointestinal hemorrhage. 14,[44][45][46] These complications should be weighed against the severity of HRS, and the absence of an effective treatment for this complication of cirrhosis. Nevertheless, prospective controlled studies in large series of patients are clearly needed, to evaluate the efficacy and incidence of side effects, before this treatment can be advocated for use in general practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these side effects were because of the powerful vasoconstrictor action of ornipressin, and were similar to the complications observed in therapeutic trials of vasopressin in cirrhotic patients with gastrointestinal hemorrhage. 14,[44][45][46] These complications should be weighed against the severity of HRS, and the absence of an effective treatment for this complication of cirrhosis. Nevertheless, prospective controlled studies in large series of patients are clearly needed, to evaluate the efficacy and incidence of side effects, before this treatment can be advocated for use in general practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vasopressin could be more useful in patients with reversed portal flow [25], Although in use as therapy of variceal hemorrhage for 25 years, the results of ran domized controlled trials are not completely convincing (table I). Three of four reported trials [26][27][28] showed a beneficial effect in upper gastrointestinal (GI) bleeding, while the last one failed to detect a statistical dif ference between placebo and vasopressin [29]. Three trials permit separate assessment of variceal and other sources, two showing an advantage of vasopressin over placebo [26,27], while the third one again failed to demonstrate such a difference [29], The neg ative study by Fogel et al [29] was an ex tremely well done study using a rather high (0.67 IU/min) initial dose and finding no improvement in control of bleeding (table I), transfusion requirements or outcome.…”
Section: Vasopressinmentioning
confidence: 99%
“…At pharmacological doses, it induces smooth muscle contraction, particularly in splanchnic arterioles, vasoconstriction of which reduces blood inflow into the portal venous system and thereby lowers the portal venous pressure. Vasopressin was compared with non-active treatment or placebo in 4 randomised controlled trials [11][12][13][14], including only 157 patients (table 1). In two of these trials the intra-arterial route of administration was used [12,13].…”
Section: Vasopressin (With and Without Nitroglycerin)mentioning
confidence: 99%